PERGESERAN LAYANAN PERPUSTAKAAN DALAM LINGKUNGAN INFORMASI YANG KOMPLEKS: REPERESENTASI LAYANAN REFERENSI DI PERPUSTAKAAN UNIVERSITAS ANDALAS (UNAND) PADANG - Vita Nova Rullis (UIN Imam Bonjol Padang, 2019)
The virtual reference service in the university library is one of the library services that has a very important function in meeting user needs. In order to meet the information needs of users that the reference service librarian has provided virtual tools as access points for users in finding the information they need, including through chatt as a virtual tool to answer specific or simple questions, giving ebook / digital reading material, recommends the web as a relevant resource as needed and can also provide an online bibliography as a resource. This article tries to describe the reference service in the Andalas University library in Padang today. Virtual reference services for visitors as information society in the postmo era then become a trend service that is very important to note, not only in terms of users in utilizing services, but also the attention of libraries in focusing the function of virtual reference services that are actually for users in college libraries.